UNCERTAINTY (AMBIVALENCE) OF CONSUMER ATTITUDES TOWARDS COUNTERFEIT PRODUCTS - MYSKO, Yuriy; SAPOZHNIK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article deals with the issues of uncertain (ambivalent) attitude of consumers to counterfeit products. The purpose of the study was to find out the reasons for this attitude. The problem of the spread of counterfeit goods has been around for a long time, since it was discovered that the Chinese were able to copy everything they saw in Europe with fantastic accuracy, and since then the fight against this problem has not stopped. Globalisation has made this problem even more urgent. The scale that the spread of counterfeit products has reached in recent decades has forced the adoption of measures to combat this problem: manufacturers develop packaging that is difficult to copy, patent compositions and manufacturing methods, and states try to address the issue by strengthening control measures and developing intellectual property rights. The article shows that one of the most obvious reasons for the deliberate purchase of counterfeit goods is economic coercion, i.e. a situation where a person cannot afford a more expensive product. However, as a number of studies show, counterfeit goods are purchased not only by people who are under economic duress. Despite the active fight against counterfeiting, demand for counterfeit goods continues to be high, although buyers are well aware of the risk of making a purchase. However, the strongest influence on the desire to buy counterfeit goods is made by the product's compliance with consumer expectations, satisfaction with the purchase, perceived risk and functionality of the product being purchased. When choosing goods for which functionality is particularly important, the purchase decision is influenced by factors such as the quality and purpose of the product, while for fashion-related goods, the purchase intention is determined more by the image and attractiveness of the product. In addition, the intention to buy counterfeit goods is influenced by the consumer's income level, and this influence is negative, as original goods are quite expensive. It is concluded that, despite the fact that the relationship between the declared attitude and the purchase of counterfeit products is negative, an ambivalent (uncertain) attitude towards counterfeiting does exist, but it is mainly due to the product category in which the purchase takes place or the situation of purchasing such products.
Keywords: counterfeiting; ambivalent attitude of consumers to counterfeiting; factors of consumer attitude to counterfeiting; factors of counterfeit consumption